Analisis Efektivitas Biaya Penggunaan Metildopa Dibandingkan Dengan Nifedipine Pada Pasien Preeklampsia Rawat Inap Di RSUD H. Abdul Manap Kota Jambi - Safitri, Wiwit Wulan; Dewi, Rasmala; Sutrisno, Deny (Jurnal Farmasi Udayana, 2021)
Hypertension in pregnancy or preeclampsia was one of the main causes of morbidity and mortality in fetuses and pregnant women. Treatment for hypertension in pregnant women must be safe and appropriate, so the treatment of preeclampsia requires special attention to obtain effective therapy at a more rational cost. One methodology that can be used to conduct pharmacoeconomic research is a cost effectiveness analysis. This study aimed to determine the most effective use of drugs between methyldopa and nifedipine in terms of costs and benefits (outcomes) resulting in inpatients of preeclampsia hospitalized at H. Abdul Manap Hospital, Jambi City. This study was designed descriptively with retrospective data collection, by taking data from the medical records of inpatients at H. Abdul Manap Hospital, Jambi City. The number of samples in this study were 67 patients. Of the 67 samples, it was shown that the use of the antihypertensive nifedipine was more effective (cost effective) than the use of the antihypertensive methyldopa in 2016-2018 at H. Abdul Manap Hospital, Jambi City. Judging from the ACER value in 2016-2018, nifedipine has a lower ACER value, namely in 2016 Rp. 6,948, in 2017 Rp. 7,035, and in 2018 Rp. 8,572.